Auroral fragmentation into patches. Issue 10 (21st October 2014) - Shiokawa, Kazuo; Hashimoto, Ayumi; Hori, Tomoaki; Sakaguchi, Kaori; Ogawa, Yasunobu; Donovan, Eric; Spanswick, Emma; Connors, Martin; Otsuka, Yuichi; Oyama, Shin‐Ichiro; Nozawa, Satonori; McWilliams, Kathryn
Abstract Auroral patches in diffuse auroras are very common features in the postmidnight local time. However, the processes that produce auroral patches are not yet well understood. In this paper we present two examples of auroral fragmentation which is the process by which uniform aurora is broken into several fragments to form auroral patches. These examples were observed at Athabasca, Canada (geomagnetic latitude: 61.7°N), and Tromsø, Norway (67.1°N). Captured in sequences of images, the auroral fragmentation occurs as finger‐like structures developing latitudinally with horizontal‐scale sizes of 40–100 km at ionospheric altitudes. The structures tend to develop in a north‐south direction with speeds of 150–420 m/s without any shearing motion, suggesting that pressure‐driven instability in the balance between the earthward magnetic‐tension force and the tailward pressure gradient force in the magnetosphere is the main driving force of the auroral fragmentation. Therefore, these observations indicate that auroral fragmentation associated with pressure‐driven instability is a process that creates auroral patches. The observed slow eastward drift of aurora during the auroral fragmentation suggests that fragmentation occurs in low‐energy ambient plasma.